Pengaruh Etika Kepemimpinan Terhadap Kinerja Guru di MAN 2 Sijunjung - Dona Ana Yori Alwis; Suswati Hendriani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to examine the influence of ethical leadership on teacher performance at MAN 2 Sijunjung. Leadership ethics includes the application of the principles of honesty, justice, responsibility, and transparency in a leader's actions. In the educational context, leadership can create a positive and supportive work environment, which ultimately influences improving teacher performance. The research method used is a qualitative approach with a descriptive design. Data was collected through in-depth interviews with teachers and madrasa leaders, direct observation in the work environment, and analysis of internal organizational documents. Research results show that teachers who work under ethical leaders report higher levels of motivation, a greater sense of job satisfaction, and better performance. Teachers feel more valued and supported, which encourages them to work harder and achieve better results. Apart from that, ethical leadership also contributes to the formation of a strong organizational culture, which encourages cooperation, openness, and innovation. The conclusion of this research is that ethical leadership has a significant influence on teacher performance at MAN 2 Sijunjung. Therefore, it is important for educational institutions to strengthen ethical leadership as part of a strategy to improve the quality of education